Dynamical, mechanical, anisotropic, and thermodynamic properties of Mg-XL-Y (XL = Zn, Al) alloys with long-period stacking ordered structures: A first-principles calculation. (February 2023) - Chen, Yingying; Zuo, Enci; Dou, Xilong; Chen, Li; Mao, Aijie; Jiang, Gang
Abstract: The dynamical, mechanical, anisotropic, and thermodynamic properties of Mg-X L -Y (X L = Zn, Al) alloys based on three long-period stacking ordered (LPSO) phases (ie, 10H, 14H, and 18R) have been investigated systematically by first-principles calculations. The LPSO phases of Mg-X L -Y (X L = Zn, Al) alloys are thermodynamically, dynamically, and mechanically stable. The each LPSO phase of Mg–Al–Y alloys has superior mechanical properties with larger resistances to deformation under applied stress and shear pressure, stiffness, as well as hardness than those of corresponding to LPSO phases of Mg–Zn–Y alloys. According to universal elastic anisotropic index, percent shear anisotropy, 3D surface structures of Young's moulus, and sound velocities, the LPSO phases of Mg-X L -Y (X L = Zn, Al) alloys exhibit obvious anisotropy. Besides, all LPSO phases of Mg-X L -Y (X L = Zn, Al) alloys possess low lattice thermal conductivity due to the strong anharmonicity. The calculated adsorption energies indicate that the 14H(001) surface of Mg–Al–Y system at the hollow site is more sensitive to absorb O atom. Highlights: Three long-period stacking ordered (LPSO) phases (ie, 10H, 14H, and 18R) are thermodynamically, dynamically, and mechanically stable. Each LPSO phase of Mg–Al–Y alloys has superior mechanical properties with larger resistances to deformation under applied stress and shear pressure, stiffness, as well as hardness than those of corresponding to LPSO phases of Mg–Zn–Y alloys. LPSO phases of Mg-X L -Y (X L = Zn, Al) alloys exhibit obvious anisotropy and low lattice thermal conductivity.